A two-step approach for selection of railway modernization projects based on analytic hierarchy process - Ković, Rajko; Milenković, Miloš (Transport, 2022)
This paper presents a simulation of the Project Portfolio Management (PPM) model usage in evaluation and selection of modernization projects of Serbian Railways. Performance review of the selected projects is conducted in regards to the strategic goals of the company, which have been established during the process of strategic planning. The project selection model is methodologically set up as a two-step selection model. The number of portfolio projects is narrowed down by ranking their importance in regards to the success of the modernization program (benefits, risks, and resources), which is followed by the ranking of the projects on the basis of their contribution to the realization of previously chosen liquidity and rentability goals, which are always a challenge when it comes to railway companies. This selection procedure is simulated by applying the Analytic Hierarchy Process (AHP), a mathematical model of linear programming, embedded in the software package “Expert Choice”. The simulation results show that, in this way, it is possible to achieve a considerable drop in the amount of necessary financial resources for the realization of modernization projects, which is also the main contribution of this paper. This proves the efficiency of the PPM concept application as a modern model of strategic management. The showcased model of project portfolio selection can find a significant usage among the current processes of railways restructuring, especially in financing of the projects of public–private partnerships.